ANALISIS STRUKTUR INTRINSIK DAN NILAI PENDIDIKAN PADA SATUA DUKUH SILADRI - I Gusti Agung Rai Jayawangsa; I Nengah Adi Widana; I Made Udayana Putra (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2021)
In Bali, the tradition of storytelling (nyatua) is not strange, as evidenced by the existence of fairy tales and folk tales that exist in the community. The story of Dukuh Siladri is interesting to study because the message of the Hindu religion is implied in the story, and the satua story can be used as a basis for self-reflection and is used by parents who guide children. This research is a qualitative study using structure theory to dissect intrinsic structure and value theory to dissect educational values. The intrinsic structure studied is the theme, character, characterization, plot, setting and mandate. Meanwhile, the educational value found was the value of religious education, namely ethics.Keywords: fairy tales (satua), intrinsic structure, educational value